IJCM_261A: Reaching the unreachable: An outreach based approach of IGMC Shimla to organise Ayushmann Health Melas/ Camps at Secondary level facilities in 03 districts of Shimla, Solan and Bilaspur in vicinity of the college - Sharma Archit; Sachdeva Amit (Wolters Kluwer Medknow Publications, 2024)
Background: Soul of India lives in its villages with >65% population living in rural settings. Saturation of all services especially Health services is at core of "leave no one behind" in line with principle of 'Antyodaya' reaching out at all. To build momentum with Pradhan Mantri Jan Arogya Yojana Ayushman Health Camps were organised by IGMC Shimla at secondary level facilities under flagship campaign Ayushman Bhavah Objective: Evaluation of health care services delivered by IGMC Shimla in Ayushmann Health Melas at secondary level facilities of 03 districts of Himachal Pradesh. Methodology: Ayushman Melas organised by IGMC Shimla at secondary level facilities from September 2023 to December 2023 in 03 districts Shimla (25); Solan (12) and Bilaspur (13) for providing clinical services to beneficiaries. Real time portal based reporting and analysis of same alongwith specialitywise footfallbifurcation is core. Results: As per Real time-based portal report analysis a footfall of 10379 registered out of which 9055 (87.24%) availed specialists services and 1324(12.74%) general physician services. A net of 2672 (29.5%) beneficiaries availed internal medicine specialist services, 458 (5.05%) surgical, 1619 (17.87%) orthopaedics, 772 (8.52%) obstetrics and gynaecology, 1460 (16.12%) Opthalmology, 698 (7.7%) Otorhinolaryngology, 152 (1.67%) psychiatry, 493 (5.44%) dermatology and 731 (8.07%) paediatric services respectively. 1012(9.75%) new diagnosed Hypertensives and 945 (9.10%) new diagnosed Diabetics, 1492 14.37%) beneficiaries screened for Oral Cancers, 804 (7.75%) for breast cancers and 468 (4.5%) for cervical Cancers. 299 (2.88%) new diagnosed cataract cases. 10379 beneficiaries were tested for 11102 tests (106.96%). Conclusion: Comprehensive health care service delivery by camps to unreachable for screening, diagnosis, one stop multi-speciality consultancy, referral and digitalisation of health vitals.